2023
DOI: 10.1101/2023.01.17.23284694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Traditional male circumcision and the risk for HIV transmission among men: a systematic review

Abstract: Introduction Although traditional male circumcision (TMC) is still practiced in a number of countries, and its healing process may have a high risk of HIV and other STIs transmission, there have been no published systematic reviews on TMC, HIV risk, and impacts on circumcised men and their families. The aim of this study is to synthesise evidence of how TMC practices contribute to HIV transmission among males and the impacts of HIV on themselves and their families. Methods The systematic search started with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Sarawak and Indonesia have both participated in the field of medical tourism. Indonesians have been seeking medical treatment in neighbouring countries, such as Sarawak, for several reasons, including the presence of healthcare services, specialized medical expertise, patient-focused care, affordability, and religious and socio-cultural considerations (Asa et al, 2024). Sarawak has shown a strong interest in promoting medical tourism with Indonesia, acknowledging the potential for growth in healthcare services and tourism prospects (Dayak Daily, 2022).…”
Section: Medical Tourism Industry Impact In the State Of Sarawakmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarawak and Indonesia have both participated in the field of medical tourism. Indonesians have been seeking medical treatment in neighbouring countries, such as Sarawak, for several reasons, including the presence of healthcare services, specialized medical expertise, patient-focused care, affordability, and religious and socio-cultural considerations (Asa et al, 2024). Sarawak has shown a strong interest in promoting medical tourism with Indonesia, acknowledging the potential for growth in healthcare services and tourism prospects (Dayak Daily, 2022).…”
Section: Medical Tourism Industry Impact In the State Of Sarawakmentioning
confidence: 99%
“…Indonesian citizens have been travelling to Sarawak to receive medical care for a variety of reasons, such as the unavailability of specific therapies in their nation, the scarcity of medical specialists, and the absence of skilled doctors in remote areas of Indonesia (Asa et al, 2024). Indonesian patients constitute around 84% of all foreign patients in Sarawak, making them the majority of foreign patients in the region (Ormond & Sulianti, 2012).…”
Section: Medical Tourism Industry Impact In the State Of Sarawakmentioning
confidence: 99%
“…Circumcision is also one of the most cost-effective and critical interventions to maintain progress towards the end of the HIV/AIDS epidemic [6] [7][8] [9]. Similarly, traditional circumcision can reduce the risk of HIV/AIDS infection in men [10]. HIV/AIDS prevention needs to achieve and maintain high circumcision coverage.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, male circumcision is increasingly recommended as a strategy to reduce HIV transmission, particularly in areas with a high prevalence of HIV. [18][19][20][21][22][23][24][25][26][27] A WHO and the United Nations report has also highlighted a correlation between the lack of male circumcision and higher HIV rates, specifically in Eastern and Southern Africa. 28 Likewise, some meta-analyses showed that male circumcision protects significantly against HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…13 43 The possibility of acquiring HIV infection through TMC is also considered high due to sharing of a surgical knife or blade on multiple men. 23 27 44-46 TMC refers to the procedure of removing the foreskin of the penis in males in a non-clinical way by traditional circumcisers without formal medical training. 47 In addition to preparing newly circumcised males for the transition to manhood, TMC symbolises new initiates officially being accepted in the community with a new status of being a man and becoming a good model in family and society.…”
Section: Introductionmentioning
confidence: 99%